30 Years of Progress toward Increased Biomass Yield of Switchgrass and Big Bluestem. Issue 3 (1st May 2018) - Casler, M. D.; Vogel, K. P.; Lee, D. K.; Mitchell, R. B.; Adler, P. R.; Sulc, R. M.; Johnson, K. D.; Kallenbach, R. L.; Boe, A. R.; Mathison, R. D.; Cassida, K. A.; Min, D. H.; et al.
Abstract : Breeding to improve biomass production of switchgrass ( Panicum virgatum L.) and big bluestem ( Andropogon gerardii Vitman) for conversion to bioenergy began in 1992. The purpose of this study was (i) to develop a platform for uniform regional testing of cultivars and experimental populations for these species, and (ii) to estimate the gains made by breeding during 1992 to 2012. A total of 25 switchgrass populations and 16 big bluestem populations were planted in uniform regional trials at 13 locations in 2012 and 2014. The reference region was USDA Hardiness Zones 3 through 6 in the humid temperate United States. Significant progress toward increased biomass yield was made in big bluestem and within upland‐ecotype populations, lowland‐ecotype populations, and hybrid‐derived populations of switchgrass. Four mechanisms of increasing biomass yield were documented: (i) increased biomass yield per se, (ii) later flowering to extend the growing season, (iii) combined later flowering from the lowland ecotype with survivorship of the upland ecotype in hybrid‐derived populations, and (iv) increased survivorship of late‐flowering lowland populations in hardiness zones that represent an expansion of their natural adaption zone. Switchgrass exhibited all four mechanisms in one or more improved populations, whereas improved populations of big bluestem were likely influenced by two of the four mechanisms. The uniform testing program was successful at documenting increases in biomass yield, identifying the mechanisms for increased yield, and determining adaptation characteristics and limitations of improved populations.